Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Di SDN 18/III Tarutung Kabupaten Kerinci - Zaki Hendra Zeki Y; Yuliana Yuliana (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2020)
This study aims to: (1) describe the role of school principals in increasing educational support through planning, organizing, and supervising school programs in SDN 18 / III Tarutung, Kerinci Regency; (2) describe the obstacles in improving the quality of education. This research is a case study using qualitative. The subjects of the study were the Principal, educators, and education staff. The results of this study indicate the role of school principals in improving the quality of education: (1) planning and initiating programs, curriculum, learning policies, counseling guidance with educators and education staff; (2) creating an organizational structure that requires parents through the school board and completing the required infrastructure; (3) educating educators and education in the administration process, and learning media; (4) disciplining educators and education personnel in the learning process from the admission process to the completion of the teaching and learning program. (5) Give a good and calm example at work, motivate and respect moral and material responsibilities, increase welfare, include educators and education personnel in training and education and motivate senior teachers to have a lifelong spirit of education; (6) Apply the principle of kinship in all activities. The constraint that speaks is the factor of facilities and infrastructure in supporting student learning activities.